Emerging monoclonal antibodies for the treatment of renal cell carcinoma (RCC). (2nd July 2016) - Atkins, Michael B.; Philips, George K.
ABSTRACT: Introduction : Advanced renal cell carcinoma (RCC) was considered refractory to most cancer therapies until the 1980s, after which immune modulating agents and targeted agents were developed. Recently the rapid development of therapeutic monoclonal antibodies targeting immune checkpoint pathways has provided significant clinical benefit in patients with many distinct cancer types. Nivolumab, an anti-PD1 monoclonal antibody showed improvement in response rate and overall survival in patients with previously treated RCC and received US FDA approval in late 2015. Current efforts with anti-PD1-based therapy include combinations with ipilimumab and with VEGF pathway blockers in the hopes on building on the activity of single agent therapy. Areas covered : We describe our current understanding of tumor immunology including the basis of the tumor-specific immune response and the adaptive mechanisms used by the tumor for immune escape. We describe the mechanisms of action as well as the therapeutic application of the antibodies, ipilimumab, nivolumab and atezolizumab in patients with RCC. We identify key areas of active research in biomarker development and combination therapies. Expert opinion : Clinical trials and the field of RCC therapeutics are expected to move in the direction of combination therapies using immune checkpoint inhibitors, extending overall survival as a benchmark for new drug approvals, and biomarker validation for improved selection of patients for specific therapies.